Light and sound sculptures: a sensory approach to art And space from architectural education - Cruz Cuentas, Ricardo Luis (2025)
This pedagogical experience with first-year architecture students focused on the creation of Light–Sound Sculptures as a means to explore spatial perception through multisensory processes. The objective was to translate musical abstraction into three-dimensional compositions, integrating form, sound, and light within a synesthetic proposal. The qualitative and experimental methodology, applied to a cohort of 20 students, was based on the analysis of a selected musical piece, transferring its attributes (expressivity, timbre and sound color, form and structure, rhythm and tempo, melody, harmony, silence and space, text and message, style and genre, as well as cultural and historical context, and listener impact) into the design of a sculptural object. The results, evaluated through design rubrics and systematic reflective analyses, demonstrate the feasibility of synesthetic translation as a pedagogical tool to strengthen the understanding of form and spatial atmosphere in architectural education. The study validates this approach as a powerful pre-compositional mechanism that transcends visual hegemony in the architectural design process.